Dividend and Agency Conflict in Indonesian Manufacturing Firms - Andi Anugerah Amrullah; Hendra Wijaya (Jurnal Keuangan dan Perbankan, 2018)
Firm’s investment and financing decision had been empirically proven to have a certain influence on firm value, as changes in investment and financing policies will result in alterations of the firm risk profile. In the case of Indonesia, where the degree of investor protection was poor, and minority shareholders were at risk of expropriation of majority shareholders, increase in investment and debt addition was ill-favored and hence, result in a lower firm value. To mitigate the risk of expropriation, firms might choose to apply cash rights to its shareholders by distributing dividends. Using panel data with moderation on 86 Indonesian manufacturing firms, we found that dividend policy positively moderates the effect of the investment decision in firm value and negatively moderates the effect of financing decision on the value of the firm. Our finding act as empirical evidence that dividend policy was an effective tool to mitigate expropriation risk, albeit its used also sent a negative signal to the shareholder when a firm increases loans to paid out dividends.JEL Classification: G31, G32.DOI: https://doi.org/10.26905/jkdp.v22i3.1820